Diskursus Pengujian Peraturan Kebijakan (Beleidsregel) oleh Peradilan Tata Usaha Negara - Muhshi, Adam; Yunita, Fenny Tria (Media Iuris, 2024)
The policy rule, or beleidsregel, is a legal instrument derived from a discretionary legal authority known as freies Ermessen. Unlike legislation and decisions, which are grounded in formal legal principles, policy regulation is based on the principle of discretion. However, in the evolution of administrative law in Indonesia, the use of discretionary power has become more formalized, blurring the lines between policy rules based on discretion and statutory regulations. Despite this, the review and testing of policy regulations continue to rely on general principles of good governance. This reliance makes it challenging for judicial institutions to review or annul policy regulations if they infringe upon citizens' rights. This paper employs a juridical-normative method, incorporating conceptual-theoretical, statutory, and comparative approaches, to evaluate and propose how the state can safeguard citizens' rights violated by policy rules. It also examines whether the judiciary should have the authority to review policy rules. The study concludes that an appropriate mechanism should be established between the reviewing body and the standards for evaluating policy rules. Furthermore, the judiciary should have the discretion to determine the standards for policy regulations, whether by applying general principles of good governance or by also considering laws and regulations that a policy regulation might violate.